Maternal influenza vaccination during pregnancy and the risk of adverse pregnancy and birth outcomes - Tchuente, Vanina; Sheehy, Odile; Muckle, Gina; Walker, Mark; Fraser, William D.; Bérard, Anick (Frontiers in Pharmacology, 2026)
BackgroundInfluenza vaccination is recommended during pregnancy. We aimed to assess pregnancy and newborns’ outcomes.MethodsParticipants were recruited in their first trimester of gestation, from 05/25/2010 to 08/30/2012. Data were collected, each trimester through telephone-administered interviews. Influenza vaccine exposure was defined as a report of AH1N1 or seasonal influenza vaccine, within 6 months before the last menstrual period or during pregnancy. To answer our different objectives, three sub-cohorts were created: a case-control study to assess the risk of spontaneous abortion (SA), a sub-cohort to assess the risk of prenatal maternal influenza, and a birth cohort to assess the risk of preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA), and infant hospitalization. Multivariate logistic regressions were used to quantify these associations.ResultsIn the case-control study (n = 418), after adjustment, no significant association was found between influenza vaccination and the risk of SA (aOR: 0.53, 95% CI: 0.10–2.68). In the sub-cohort of 2,114, 10.0% were exposed to influenza vaccine. Maternal influenza-like symptoms prevalence was 26.5% in the vaccinated group and 25.8% in the unvaccinated group. No significant association was found between the risk of prenatal influenza and influenza vaccine (aOR: 0.92, 95%CI: 0.66–1.29). In the birth cohort of 2,046, 13.9% newborns were exposed in-utero to influenza vaccine. No significant association was found between influenza vaccination and the risk of PTB (aOR: 1.30, 95%CI 0.77–2.19), SGA (aOR: 1.13, 95%CI 0.71–1.79), LBW (aOR: 0.94, 95%CI 0.31–2.26), all-cause hospitalization (aOR: 1.02, 95%CI 0.65–1.61).ConclusionInfluenza immunization during pregnancy does not seem to be associated to pregnancy and birth adverse effects.